The Personality Characteristics of Counsellors-in-Training which Correlate with Ratings of Effectiveness and Grades - Leard, Hugh M.; Hum, Andrew (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this investigation was to examine the relationship between four commonly utilized criteria of counsellor effectiveness and personalities of the students being rated. Measures of the students' personality obtained from the Myers-Briggs Type Indicator, the Edwards Personal Preference Schedule and the 16 Personality Factor Questionnaire were correlated with three ratings of counsellor effectiveness obtained from professors, supervisors and peers and a comprehensive examination grade. Sixty graduates of a Master's degree program in counselling were included in the study. The personality variables which were related to the criteria differed noticeably for male and female counsellors. The factors which are correlated with the effectiveness ratings of faculty members were different from those which correlated with the judgments of supervisors and peers. The final leaving examination grades were significantly correlated with some personality characteristics of the male counsellors. They were not significantly related, however, to any female personality variable or any other criterion rat¡ng for male or female students.